2019
DOI: 10.1038/s41467-019-11832-3
|View full text |Cite
|
Sign up to set email alerts
|

Switchable magnetic bulk photovoltaic effect in the two-dimensional magnet CrI3

Abstract: The bulk photovoltaic effect (BPVE) rectifies light into the dc current in a single-phase material and attracts the interest to design high-efficiency solar cells beyond the pn junction paradigm. Because it is a hot electron effect, the BPVE surpasses the thermodynamic Shockley–Queisser limit to generate above-band-gap photovoltage. While the guiding principle for BPVE materials is to break the crystal centrosymmetry, here we propose a magnetic photogalvanic effect (MPGE) that introduces the magnetism as a key… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
156
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(163 citation statements)
references
References 59 publications
(75 reference statements)
6
156
1
Order By: Relevance
“…Here, we point out that the recent theoretical studies have demonstrated that AFM ordering in a bilayer CrI breaks both time-reversal ( T ) and inversion ( P ) symmetries, leading to a giant nonreciprocal second-harmonic generation 35 and a magnetic photogalvanic effect 36 . In the underlying crystallographic structure, the inversion symmetry is preserved, but the AF ordering of the two FM layers within a bilayer breaks it, eliminating the need for the non-centrosymmetric crystal.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Here, we point out that the recent theoretical studies have demonstrated that AFM ordering in a bilayer CrI breaks both time-reversal ( T ) and inversion ( P ) symmetries, leading to a giant nonreciprocal second-harmonic generation 35 and a magnetic photogalvanic effect 36 . In the underlying crystallographic structure, the inversion symmetry is preserved, but the AF ordering of the two FM layers within a bilayer breaks it, eliminating the need for the non-centrosymmetric crystal.…”
Section: Resultsmentioning
confidence: 86%
“…The future experimental studies of the electronic structure of thin flakes or films would offer a better insight into the development of dimensionality in these materials. Also, this would allow to study some truly exotic phenomena, predicted to occur at some thicknesses, including a giant nonreciprocal second-harmonic generation 35 and the creation of dc current by a linearly polarised light 36 in an AFM bilayer of CrI .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This distinction is lost in compounds which break T , as pointed out by Ref. [21] very recently, where both shift and injection current might arise for either linear or circular polarized light. While the nonlinear currents created by the incident light usually lead to Joule heating in the sample, it is possible in experiment to subtract this effect.…”
Section: A Overviewmentioning
confidence: 91%
“…Thus far, research on BPVE focuses on nonmagnetic materials. However, recent theoretical [21] and experimental [22][23][24] works on magnetic systems reveal a distinct photocurrent and second harmonic generation which cannot be merely derived from the Berry phase. Therefore, we are motivated to reexamine the second-order response theory and investigate the effects of time-reversal-symmetry (T ) breaking.…”
Section: Introductionmentioning
confidence: 99%